(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study investigates the influence of digital learning facilities and technology use on the learning motivation of junior and senior high school students, with digital literacy serving as an intervening variable, at Global Nusantara School Jakarta. Conducted in the context of the industrial revolution 4.0, where technology integration in education is imperative, the research adopts a quantitative approach utilizing path analysis via Smart PLS. The entire population of 69 students was sampled using saturated sampling. Results revealed that digital learning facilities significantly enhance digital literacy, which, in turn, indirectly boosts learning motivation. While technology use positively affects digital literacy, its direct impact on learning motivation was not significant. Digital literacy emerged as a critical mediating factor, linking digital learning facilities to enhanced student motivation. This study contributes theoretically by highlighting the importance of digital infrastructure in multicultural educational settings and practically by recommending inclusive technology policies, optimizing digital resources, and fostering teacher-student collaboration to improve learning outcomes. These findings are intended to guide modern educational management in addressing digital-era challenges effectively.